Kualitas Produk dan Penataan Barang terhadap Minat Pembelian Ulang pada Minimarket - Markus Markus (IPM2KPE, 2022)
This study aims to determine how the influence of product quality and product arrangement on repurchase intentions at Indomaret Pagar Alam. This research method is quantitative. The sample in this study were 70 respondents who were consumers of Indomaret Pagar Alam. The sampling method used by the researcher is incidental sampling. Data analysis used multiple linear regression analysis technique which was processed using SPSS V.23 application. The results showed, the results of the t test of the product quality variable with t count > from t table, namely 6.195> 0.236. In conclusion, product quality has a positive and significant effect on repurchase intention. The arrangement of goods has a positive and significant effect on repurchase interest. Keywords: Product Quality, Repurchase Intention, Goods Arrangement